Pengaruh Tingkat Pemahaman dan Kepercayaan terhadap Minat menggunakan Bank Syariah: Studi Masyarakat Desa Karang Berahi Kecematan Pamenang Kabupaten Merangin - Riduan Riduan; A.A Miftah; M.Taufik Ridho (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In Indonesia, the first sharia bank established in 1992 was Bank Muamalat Indonesia (BMI). Even though the development is a bit late when compared to other Muslim countries, sharia banking in Indonesia will continue to develop, if in the period 1992 - 1998 there was only one unit of Sharia Bank, then in 2005, the number of sharia banks in Indonesia had increased to 20 units. , namely 3 sharia commercial banks and 17 business units. Based on the data processing carried out in this research, the results were obtained for the variable Level of Understanding (X1) partially, namely with a significance level smaller than 0.05, namely with a significance level of 0.001, so it can be said that the variable Understanding has a significant influence on interest in using Islamic banks. Meanwhile, for the Trust variable (X2) partially, with a significance level smaller than 0.05, namely with a significance level of 0.040, it can be said that the trust variable influences interest in using Islamic banks. Furthermore, by using the F test to obtain a significance value of 0.001 which is smaller than 0.05, the regression model is usually used to predict that the level of understanding and trust together influence interest in using Islamic banks. The calculation of the coefficient of determination results in showing that all independent variables, namely Understanding (X1) Trust (X2) can explain the variable Interest in Using Sharia Banks (Y) by 20%, the remaining 80% is influenced by other variables not examined in this research.